2010
DOI: 10.4065/mcp.2009.0672
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pregnancy on Postural Tachycardia Syndrome

Abstract: P ostural tachycardia syndrome (POTS) is defined as the development of orthostatic symptoms associated with an increase in heart rate (HR) greater than 30 beats/min. More severe cases are associated with a standing HR increase greater than 120 beats/min. 1 Orthostatic symptoms most often include light-headedness, palpitations, presyncope, and exacerbations with heat or exercise. 2 Overall, the prognosis of POTS has been reported to be favorable in follow-up studies, with 80% of patients reporting improvement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 18 publications
2
18
1
1
Order By: Relevance
“…In our patient there was no worsening of symptoms. Similarly, the symptoms remained unchanged in 84% and 88% of parous and nulliparous patients, respectively, in a study by Kimpinski et al 2 However, Glatter et al showed progressive worsening beyond six months gestation in two of his patients with severe POTS which was attributed to physiological peak increase in heart rate which will worsen POTS. In contrast, some studies showed improvement in the later part of pregnancy due to increased fluid retention which occurs during this period.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In our patient there was no worsening of symptoms. Similarly, the symptoms remained unchanged in 84% and 88% of parous and nulliparous patients, respectively, in a study by Kimpinski et al 2 However, Glatter et al showed progressive worsening beyond six months gestation in two of his patients with severe POTS which was attributed to physiological peak increase in heart rate which will worsen POTS. In contrast, some studies showed improvement in the later part of pregnancy due to increased fluid retention which occurs during this period.…”
Section: Discussionmentioning
confidence: 93%
“…Adverse pregnancy events were similar to those seen in the general public and do not present a barrier to women with POTS who want to have children. 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PoTS does not appear to increase the rate of preterm delivery, perinatal mortality or still‐birth compared with the background rate . Reassuringly, the rate of miscarriage in women with PoTS appears to be no greater than that of the general population . However, women with PoTS have a higher rate of severe vomiting or hyperemesis gravidarum in the first trimester (50–60%) compared with the general population .…”
Section: Effect Of Postural Tachycardia Syndrome On Pregnancymentioning
confidence: 93%
“…14,15 Reassuringly, the rate of miscarriage in women with PoTS appears to be no greater than that of the general population. 20 However, women with PoTS have a higher rate of severe vomiting or hyperemesis gravidarum in the first trimester (50-60%) compared with the general population. [14][15][16] If this does occur, patients need close observation of haemodynamic status, fluid replacement, treatment with anti-emetics and consideration of thrombotic risk.…”
Section: Effect Of Postural Tachycardia Syndrome On Pregnancymentioning
confidence: 99%